STUDI KASUS: PENDAMPINGAN PERUBAHAN TINGKAH LAKU SISWA DI SMP NEGERI 25 KOTA BENGKULU - Yunarman, Sepri; Puja Amelia, Tri; Nurhasanah Pulungan, Widiya; Nurkholis, Ahmad (FAKULTAS TARBIYAH UNIVERSITAS QOMARUDDIN GRESIK - JAWA TIMUR, 2025)
This research aims to analyze the mentoring process carried out at SMP Negeri 25 Bengkulu City in order to change student behavior. This study focuses on identifying factors that influence changes in student behavior, the mentoring methods used, and the impact felt by students, teachers and the school environment. Using a descriptive qualitative approach, data was collected through observation, interviews with students and teachers, as well as analysis of related documents. The research results show that a personal approach, based on open communication, and the application of positive values are the keys to changing student behavior at SMP Negeri 25.